Immune function in newborns with in-utero exposure to anti-TNFα therapy - Weiss, Batia; Ben-Horin, Shomron; Lev, Atar; Broide, Efrat; Yavzori, Miri; Lahat, Adi; Kopylov, Uri; Picard, Orit; Eliakim, Rami; Ron, Yulia; Avni-Biron, Irit; Yerushalmy-Feler, Anat; et al. (Frontiers in Pediatrics, 2022)
Background and aim Anti-TNFα is measurable in infants exposed in utero up to 12 months of age. Data about the exposure effect on the infant’s adaptive immunity are limited. We aimed to prospectively evaluate the distribution and function of T and B cells, in infants of females with inflammatory bowel disease, in utero exposed to anti-TNFα or azathioprine. Methods A prospective multi-center study conducted 2014–2017. Anti-TNFα levels were measured in cord blood, and at 3 and 12 months. T-cell repertoire and function were analyzed at 3 and 12 months by flow-cytometry, expression of diverse T cell receptors (TCR) and T-cell receptor excision circles (TREC) quantification assay. Serum immunoglobulins and antibodies for inactivated vaccines were measured at 12 months. Baseline clinical data were retrieved, and 2-monthly telephonic interviews were performed regarding child infections and growth. Results 24 pregnant females, age 30.6 (IQR 26.5–34.5) years were recruited, 20 with anti-TNFα (infliximab 8, adalimumab 12), and 4 with azathioprine treatment. Cord blood anti-TNFα was higher than maternal blood levels [4.3 (IQR 2.3–9.2) vs. 2.5 (IQR 1.3–9.7) mcg/ml], declining at 3 and 12 months. All infants had normal number of B-cells (n = 17), adequate levels of immunoglobulins (n = 14), and protecting antibody levels to Tetanus, Diphtheria, Hemophilus influenza-B and hepatitis B (n = 17). All had normal CD4+, CD8+ T-cells, and TREC numbers. TCR repertoire was polyclonal in 18/20 and slightly skewed in 2/20 infants. No serious infections requiring hospitalization were recorded. Conclusion We found that T-cell and B-cell immunity is fully mature and immune function is normal in infants exposed in utero to anti-TNFα, as in those exposed to azathioprine. Untreated controls and large-scale studies are needed to confirm these results.